Genomic characterization of norovirus and Sapovirus from a diarrhea outbreak in a school linked to heavy rainfall - Fu, Zhongyan; Wu, Changjing; Yu, Yinghui; Zhao, Jian; Dong, Yan; Liu, Wei; Dou, Huixin; Shi, Xuezhen; Cai, Chengzhi; Jiao, Baihai; Liu, Tiantian; Jiao, Boyan (Frontiers in Microbiology, 2025)
BackgroundDiarrhea poses a serious threat to human health, and rainfall is known to increase the incidence of diarrheal diseases. On July 7, 2024, a diarrhea outbreak occurred in a school in Sishui County, Jining City, Shandong Province, China, following heavy rainfall. This study aimed to identify the pathogens responsible for the outbreak and characterize their whole genomes.MethodsOn July 8, 2024, a total of 21 stool samples from diarrhea cases, 2 water samples from private wells, and 1 drinking water sample from the school cafeteria were collected. Real-time quantitative PCR was used to detect Rotavirus A (RV-A), Norovirus genogroup I (NV GI), Norovirus genogroup II (NV GII), Sapovirus (SaV), Human Astrovirus (HAstV), and Human Adenovirus (HAdV). Whole-genome sequencing was performed for NV GI and SaV-positive samples to determine their genotypes, construct phylogenetic trees, and analyze amino acid variation sites in encoded proteins.ResultsAmong the 21 case stool samples, 7 tested positive for both NV GI and SaV, 10 were positive for NV GI only, and 1 was positive for SaV only. Of the 2 private well water samples, one was positive for NV GI and the other for SaV. Whole-genome sequences were obtained for 11 NV GI strains and 2 SaV strains. The 11 NV GI sequences from the outbreak exhibited high homology, with whole-genome similarity ranging from 99.96% to 100%, and were all identified as the NV GI.6 [P11] genotype. Phylogenetic analysis showed that these 11 sequences clustered within the same evolutionary branch. Similarly, the 2 SaV sequences were highly homologous, with 99.97% similarity, and were identified as the SaV GI.6 genotype, clustering within the same phylogenetic branch.ConclusionsThis diarrhea outbreak was caused by the combined presence of NV GI and SaV following heavy rainfall. These findings provide valuable reference data for the prevention and control of diarrhea outbreaks caused by heavy rainfall or multiple pathogens.